E-138 The value of perfusion ct as a prognostic factor after mechanical thrombectomy in anterior circulation large vessel occlusion patients. (22nd July 2018) - Moon, B
Abstract : Introduction: Mechanical thrombectomy is recommended as first line treatment for large vessel occlusion(LVO) patients. Mechanical thrombectomy is performed based on the ASPECT score to achieve recanalization of the blood vessels at a faster rate. However, in patients with ASPECT score of 6 or more, the infarction volume on the diffusion MRI can occur throughout the MCA territory, resulting in hemorrhage after the thrombectomy and low cost effectiveness. Therefore, we conducted a study to determine whether recanalization was faster and whether perfusion CT could be used as a predictor of prognosis. Method and material: We retrospectively studied patients who had recanalization therapy with LVO of anterior circulation at our hospital from 2011 to 2015. The cerebrovascular accident(CVA) protocol was activated when LVO was suspected, and non-enhance CT, perfusion CT, and CT angiography were performed. The CVA CT scan takes a 7 min. In these patients, 10 areas such as ASPECT score were designated and scores were given to the lowered areas of CBF, MTT, and CBV compared with the contralateral side, and scoring was performed at 10 points. EMR and imaging study of patients with ASPECT score of 7 or more were confirmed. We checked NIHSS at admission, mRS at discharge, and mRS at 90 days after discharge. Results: In total, 94 patients met the inclusion criteria of this study. After recanalization, TICI G 2b and 3 were achieved 80 patients (85.10%). Of the total patients, 71 patients (75.53%) had a CBV score of 4points or less and 23 patients (24.47%) had a score of 5points or more. In patients with CBV 4 points or less, good outcome (mRS 0˜2) was 34 patients (47.88%). In patients with CBV 5 points or more, good outcome (mRS 0˜2) was 6 patients(26.08%). The mortality rate was 7.04% (5 patients) in patient with CBV 4points or less, but there were 30.43% (7 patients) in patients with CBV 5points or more. Conclusion: Mechanical thrombectomy showed better prognosis in LVO patients with CBV score of 4 points or less. But there is showed higher mortality rate in patients with CBV score of 5 points or more. Perfusion CT can be helpful in predicting the prognosis of the patient. Disclosures: B. Moon: None.